Mucinous cystic neoplasms of the pancreas: A Surgical Disease - Hackert, Thilo; Michalski, Christoph; Büchler, Markus W. (JAMA surgery, 2017)
The study by Postlewait and coworkers1 presents the largest series of surgically treated mucinous cystic neoplasms (MCNs) of the pancreas to date. Eight academic centers in the United States have contributed to this cohort, and the authors show an overall malignancy rate of 15% mostly associated...
Gesehen am 24.09.2018